Karakteristik anemia pada lansia di RSUP Sanglah Denpasar pada bulan Januari-Juni 2017 - Alvi Laili Zahra; Ida Bagus Putu Putrawan; Tjokorda Gde Dharmayuda (DiscoverSys Inc., 2019)
Background: Anemia is a symptom depending on the decrease of hemoglobin levels, the number of erythrocytes, and the volume of erythrocytes. The symptoms of anemia commonly occur in the elderly. In general, the common causes that often complained in the elderly are less efficient in absorbing some of the nutrients, decreased appetite due to illness, difficulty swallowing due to reducing of saliva, slow feeding, reduced teeth, and nausea. Anemia in the elderly should not be considered as an unavoidable consequence of aging. Treatment of this problem should start as early as possible.Aim: This study aims to determine the characteristics of anemia in the elderly in RSUP Sanglah from January to June 2017.Method: This research is a descriptive cross sectional study conducted at RSUP Sanglah Denpasar. Data obtained in the form of secondary data patient record period JanuaryÂ - June 2017. Data were analyzed using Microsoft Excel 2010.Result: Of the 102 patients, the average age was 69.3 Â± 7.1 years with the highest proportion of patients aged 60-70 years old is 56 people (54.9%). The proportion of male is 71 people (69,6%). Of the total samples, there were 75 patients anemia patientsÂ (73.5%) and 27 patients without anemia (26.5%). The highest proportion of anemia depend on their stages are 51 patients of mild anemia (68%). 47 patients (62.7%) were normochromic and normocitary anemia. The highest proportion is anemia with kidney disease (38,7%).